Filarial Coinfection Is Associated With Higher Bacterial Burdens and Altered Plasma Cytokine and Chemokine Responses in Tuberculous Lymphadenitis - Kathamuthu, Gokul Raj; Munisankar, Saravanan; Banurekha, Vaithilingam V.; Nair, Dina; Sridhar, Rathinam; Babu, Subash (Frontiers in Immunology, 2020)
Filarial infections are known to modulate cytokine responses in pulmonary tuberculosis by their propensity to induce Type 2 and regulatory cytokines. However, very little is known about the effect of filarial infections on extra-pulmonary forms of tuberculosis. Thus, we have examined the effect of filarial infections on the plasma levels of various families of (IL-1, IL-12, C and regulatory) cytokines and (CC and CXC) chemokines in tuberculous lymphadenitis coinfection. We also measured lymph node culture grades in order to assess the burden of Mycobacterium tuberculosis in the two study groups [Fil+ (n=67) and Fil- (n=109)]. Our data reveal that bacterial burden was significantly higher in Fil+ compared to Fil- individuals. Plasma levels of IL-1 family (IL-1, IL-, IL-18) cytokines were significantly lower with the exception of IL-33 in Fil+ compared to Fil- individuals. Similarly, plasma levels of IL-12 family cytokines -IL-12 and IL-23 were significantly reduced, while IL-35 was significantly elevated in Fil+ compared to Fil- individuals. Filarial infection was also associated with diminished levels of IL-2, IL-9 and enhanced levels of IL-4, IL-10 and IL-1Ra. Similarly, the Fil+ individuals were linked to elevated levels of different CC (CCL-1, CCL-2, CCL-3, CCL-11) and CXC (CXCL-2, CXCL-8, CXCL-9, CXCL-11) chemokines. Therefore, we conclude that filarial infections exert powerful bystander effects on tuberculous lymphadenitis, effects including modulation of protective cytokines and chemokines with a direct impact on bacterial burdens.